INFLUENCE OF FORMALDEHYDE AS A FACTOR OF THE ENVIRONMENT FOR THE DEVELOPMENT OF HYPOTHIREOSIS AND RELATED DISORDERS ESTROGEN SYNTHESIS - Тішков, Олександр; Петряник, Софія (Modern engineering and innovative technologies, 2023)
The article analyzes the impact of atmospheric air quality, in particular the presence of such a pollutant as formaldehyde, on the reproductive function of the female body; established a connection between the presence of formaldehyde in the environment a